Community Empowerment Through Training on Making Sago Biscuit in Gwinjaya Village, Bonggo District, Sarmy Regency, Papua Province - Gunaedi, Tri Gunaedi; Lisye Iriana Zebua; Meinarni Asnawi; Tri Wiyono (IJCS: International Journal of Community Service, 2023)
Gwinjaya is a village in Bonggo District, developed from the SP4 (Settelement Unit) transmingration settlement land in Bonggo district. The people mainly make their living as farmers and mostly grow peanuts and cultivating sago flour which comes from the sago plant. The abundant harvest has not yet been processed into food which has a higher selling value and is more durable. Through training in making biscuits made from sago flour and peanuts as well as sugar and spices , it is hoped that new etreprenuers can be formed with biscuit sago commodities. Tha training was carried out by demonstrating biscuit making and continued with participants trying to make biscuits. The resulting product was then tested organaoleptically to determine the quality and preference of the biscuits produced compared to biscuits sago sold on the market. The results of the activities that have been carried out show that the mothers in the village Gwinjaya, which is part of the Gwinjaya Village-Owned Enterprices , has been able to make biscuits made from sago flour well. The results of organoleptic testing produced with three other biscuit products on the market, showing that the respondents expressed their liking for the products they produced as seen from taste, smell, aroma and color parameters